Investigation of the absorption coefficient, refractive index, energy band gap, and film thickness for Al0.11Ga0.89N, Al0.03Ga0.97N, and GaN by optical transmission method - Naser M., Ahmed; Zaliman, Sauli; Uda, Hashim; Yarub, Al-Douri (Universiti Malaysia Perlis, 2009)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008 & vol. 2; issue 1 & 2, 2009.